2007
DOI: 10.1902/jop.2007.070095
|View full text |Cite
|
Sign up to set email alerts
|

A Determination of the Range of Oral Conditions Submitted for Microscopic and Direct Immunofluorescence Analysis

Abstract: Approximately half of biopsies of oral conditions that clinically resembled typically DIF-positive vesiculobullous diseases did not yield positive findings on DIF testing. Instead, a wide range of oral diseases can mimic these lesions clinically. With the exception of pemphigus vulgaris, DIF is essential for establishing a definitive diagnosis for known DIF-positive diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 16 publications
0
23
0
Order By: Relevance
“…The similarities between CUS and erosive OLP both clinically and histologically make it impossible to establish a definitive diagnosis by H&E evaluation alone. 19 Both diseases may have skin lesions as well and cause painful, burning, generalized ulcerative erythematous lesions in the oral mucosa, most commonly located on the buccal mucosa, gingiva, and tongue. However, unlike OLP, remission is rare in CUS, and only palliative treatment is available.…”
Section: Discussionmentioning
confidence: 99%
“…The similarities between CUS and erosive OLP both clinically and histologically make it impossible to establish a definitive diagnosis by H&E evaluation alone. 19 Both diseases may have skin lesions as well and cause painful, burning, generalized ulcerative erythematous lesions in the oral mucosa, most commonly located on the buccal mucosa, gingiva, and tongue. However, unlike OLP, remission is rare in CUS, and only palliative treatment is available.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report has shown that Candida smear using methylene blue was useful in detecting acantholytic cells in such cases [91]. Some studies found that the efficacy of H&E staining alone in diagnosing PV is probably greater than 90% and could be considered satisfactory [92,93]. However, ambiguous cases and treatment planning remain challenging.…”
Section: Discussionmentioning
confidence: 99%
“…DIF findings for LP are useful so as to rule out other mucocutaneous diseases. The findings are nonspecific but supportive if fibrin or fibrinogen deposition is found in the basement membrane zone (BMZ) in a linear pattern (Lo Russo et al, 2008;Rinaggio et al, 2007;Yih et al, 1998). It may not be necessary to routinely conduct DIF testing, since the histopathological findings of LP are usually diagnostic.…”
Section: Oral Lichen Planusmentioning
confidence: 89%
“…Histopathologically, MMP is characterized by subepithelial bulla formation (Lo Russo et al, 2008;. In the DIF testing of MMP patients, the linear deposition of C3, IgG or other immune globulin is observed in the BMZ (Lo Russo et al, 2008;Rinaggio et al, 2007;Yih et al, 1998). Multiple target antigens of MMP were identified in BMZ components by circulating autoantibodies in the patients' serum.…”
Section: Mucous Membrane Pemphigoidmentioning
confidence: 99%
See 1 more Smart Citation